German jihad : on the internationalization of Islamist terrorism - Steinberg, Guido, 1968- (Columbia studies in terrorism and irregular warfare., 2013)
Since 2007, the German jihadist scene has become Europe's most dynamic, characterized by an extreme anti-Americanism, impressive international networks, and spectacular propaganda. German jihadists travel to Turkey, Chechnya, Pakistan, and Afghanistan, trading in jihadist ideologies and allying themselves with virulent organizations. Mapping the complicated interplay between jihadists' personal motivations and the goals and strategies of the world's major terrorist groups, Guido Steinberg provides the first analysis of German jihadism, its links to Turkey, and its growing, global operatio.